Quasicrystal: a low-frictional novel material - Yadav T.P.; Mukhopadhyay N.K. (My University, 2025)
Complex intermetallics such as quasicrystals, a relatively new class of solid state materials have attracted considerable attention; because they have a long-range quasiperiodic order but no three-dimensional translational periodicity. The high density of tetrahedral interstitial sites displayed by metallic alloys with quasicrystalline structure makes such materials of technological interest in the field of hydrogen storage capabilities. The physical properties such as frictional properties of quasicrystalline materials are more exciting because the structures of quasicrystal are different from the both conventional crystalline and amorphous phases. This article summarizes the general overview of the research conducted in the field of frictional properties of various quasiperiodic intermetallic systems. We also describe situations where the surface elements exhibit a quasiperiodic structure opening up the possibility of extending our understanding of the relation between quasiperiodicity and the frictional properties of such structurally and chemically complex solids. © 2018 Elsevier Ltd